El Excentrico, 1979-06-05 - Garcia, Bert:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2024)
June 5, 1979 [5 de de junio de 1979]. Ano 30, No 5. Cover contains a portrait of performer Lucha Villa. The headline reads, "Radio Kaza Presents their Annual Fourth of July Picnic with the Stars Headlining Cepillin and Lucha Villa."